GIS and remote sensing-based wildlife habitat suitability analysis for Mountain Nyala (Tragelaphus buxtoni) at Bale Mountains National Park, Ethiopia - Mamush Masha; Gemechu Tadila; Elias Bojago (Quaternary Science Advances)
Ethiopia's Bale Mountains National Park protects the continent's largest remaining alpine environments. This park was first suggested in 1973 to safeguard its great biodiversity, including the endangered Mountain Nyala (Tragelaphus buxtoni) and Red Foxes. Despite these conservation measures, the lack of infrastructure and the enormous area projected have resulted in significant wildlife habitat fragmentation. The purpose of this study is to analyse the habitat suitability of the Mountain Nyala in Bale Mountains National Park using GIS and remote sensing approach in order to inform conservation efforts and assist park management seekers in making policy decisions. To identify potential habitats for the Mountain Nyala, the study employed GIS spatial analyst techniques such as the Digital Elevation Model (DEM) and Landsat 9 (OLI/TIRS) data, as well as key environmental factors such as vegetation types, soil types, topographic factors (elevation and slope), climate factors (temperature), and proximity factors (distance to settlements, roads, and rivers). The Weights of these factors was calculated using IDRISI32 Multi-Criteria Evaluation (MCE) with the pair-wise comparison method. These weighted factor maps were then integrated through weighted overlay analysis to model wildlife habitat suitability. The analysis revealed five classes of habitat suitability; of the total land area studied, 1326.7 km2 (60%) was deemed suitable for the Mountain Nyala while 881.3 km2 (40%) was unsuitable. Specifically, 327.4 km2 (15%) was classified as highly suitable, 240.7 km2 (11%) as moderately suitable, 758.6 km2 (34%) as marginally suitable, 352.4 km2 (16%) as currently not suitable, and 528.9 km2 (24%) as permanently not suitable. The majority of suitable habitats are concentrated in the northern part of the park, along the western border, and in the Harrena forest area. This study provides vital insights into habitat suitability that are crucial for the conservation of the Mountain Nyala and the overall management of the park.